Metal Metalloproteinase 2 is Differentially Regulated by the Interplay between Glucose and Insulin - Tsai Jen-Ning; Huang Yi-Ching; Chang Yih-Hsin; Shiau Ming-Yuh (International Journal of Eating and Weight Disorders, 2018)
Pre-adipocytes are the precursors with the potential to make new fat cells during adipose tissue expansion. Nevertheless, the pre-adipocytes behaviors, and their possible roles in energy homeostasis have long been overlooked. Our previous study implicates that interleukin-4 (IL-4) plays a positive metabolic role by promoting insulin sensitivity and inhibiting lipid accumulation. Besides, abundant evidence shows the involvement of matrix metalloproteinase-2 (MMP-2) in the process of adipose tissue expansion. The present study aimed at examining the cross talk among glucose, insulin and IL-4 on regulating MMP-2 expression and activity in 3T3-L1 pre-adipocytes. Effects of insulin and/or IL-4 on MMP-2 expression and activity were examined in pre-adipocytes under euglycemic or hyperglycemic environment by RT-PCR and gelatin zymography, respectively. Our results revealed that glucose level is a pre-requisite for pre-adipocytes responding to insulin and/or IL-4 treatment. In high glucose-containing environment, short-term acute insulin treatment (AI) and long-term chronic insulin exposure (CI) showed opposite regulation to MMP-2 expression and activity. Interestingly, the dominant MMPs regulatory role of CI under euglycemic condition was attenuated in cells exposed to high glucose concentration. Our results suggest pre-adipocytes may participate in the process of increasing adiposity, diabetic onset and diabetic complications through ECM alterations resulted from the insulin- and/or glucose- mediated changes of MMP-2 activity. The present study uncovers novel observations regarding pre-adipocytes behaviors.
Keywords: glucose